Comparing the utility of fishery‐independent and fishery‐dependent methods in assessing the relative abundance of estuarine fish species in partial protection areas. (30th August 2016) - Ochwada‐Doyle, F. A.; Johnson, D. D.; Lowry, M.
Abstract: In partial protection management areas such as Recreational Fishing Havens (RFHs) where commercial fishing is prohibited there are fewer sampling methods available for quantifying the relative abundance of species. Consequently, a framework is needed in such areas to decide whether sampling should be based on: (1) fishery‐independent techniques; (2) fishery‐dependent methods that rely on recreational fishery harvests; or (3) a combination of the two. This study compared fishery‐independent data derived from baited remote underwater video stations (BRUVS) and independent fishing surveys (IFS) with fishery‐dependent data based on recreational angler surveys (AS) to identify the fish species that were best enumerated by each method in two Australian RFHs. Each method captured/detected disparate species and each consistently showed correlations with the relative abundance of particular suites of species. The species that were correlated with and best enumerated by BRUVS were Microcanthus strigatus (Cuvier) and Pelates sexlineatus (Qouy & Gaimard); those correlated with IFS were Gerres subfasciatus Cuvier, Girella tricuspidata (Qouy & Gaimard), Mugil cephalus L. and Pomatomus saltatrix (L.); and those correlated with AS were Platycephalus fuscus Cuvier and Acanthopagrus australis (Owen). By identifying the species that were best quantified by each method, this study facilitates accurate monitoring of key species within RFHs.